Τὸ καλόν as a Criterion for Evaluating Innovation (τὸ καινόν) in Greek Theory of Musical Education: “Ancient” versus “New” Music in Ps. Plut. De musica - Gostoli, Antonietta (Peitho. Examina Antiqua, 2017)
The Pseudo-Plutarchan De musica provides us with the oldest history of Greek lyric poetry from the pre-Homeric epic poetry to the lyric poetry of the fourth century B.C. Importantly, the work contains also an evaluation of the role of music in the process of educating and training the citizens. Ps. Plutarch (Aristoxenus) considers the καλόν in the aesthetic and ethical sense, which makes it incompatible with the καινόν dictated by the new poetic and musical season.